Employment relations and national culture : continuity and change in the age of globalisation - Pot, Ferrie, 1969- (Cheltenham, UK ; Northampton, Mass. : Edward Elgar Pub., 2000)
Historically, alternative models of the employment relationship have developed across culturally diverse nation states. However, the trend towards globalization incorporates a powerful force towards an international uniformity of employment relations. Underlying the issues addressed in this book is the question of how important cultural differences are and will continue to be. Ferrie Pot analyzes the impact of national culture on the way the employment relationship is organized using case studies from the United States and the Netherlands. Evidence from these countries suggests that nations respond to globalization in line with their cultural values. As such, this book challenges the widespread belief that global trends will lead to the homogenization of the employment relationship.
Includes bibliographical references (p. 202-222) and index.
rpm 30/05/14
Loans
Keywords: Industrial relations -- Cross-cultural studies; International trade -- Social aspects; Industrial relations -- Netherlands -- Case studies; Foreign trade and employment; Comparative industrial relations; Industrial relations -- United States -- Case studies